Formulation and characterization of ketoprofen embedded polycaprolactone microspheres using solvent evaporation method - Pankaj Wagh; Jitendra B Naik (International Association of Physical Chemists (IAPC), 2015)
The purpose of this study was to prepare polymeric microspheres containing Ketoprofen (KFN) by single emulsion [oil-in-water (o/w)] solvent evaporation method. Polycaprolactone (PCL), biocompatible polymer, was used for the preparation of sustained released microspheres of KFN. A Plackett-Burman design was employed by using the Design-Expert® software (Version- 9.0.3.1, Stat-Ease Inc., Minneapolis, MN). Eleven factors out of six processing factors were investigated in order to enhance the encapsulation efficiency (EE) of the microspheres. The resultant microspheres were characterized for their size, morphology, EE, and drug release. Imaging of particles was performed by field emission scanning electron microscopy. Interaction between the drug and polymers were investigated by Fourier transform infrared (FTIR) spectroscopy, X-ray powder diffractometry (XRPD) and Differential Scanning Calorimetry (DSC). Graphical and mathematical analyses of the design showed that concentration of factor PCL (B) and varying speed (F, revolution per minute, rpm) were significant negative effect on the EE and identified as the significant factor determining the EE of the microspheres. The microspheres showed high % EE (31.18 % to 96.81 %). The microspheres were found to be discrete, oval with porous surface. The FTIR analysis confirmed no interaction of KFN with the polymer. The XRPD revealed the dispersion of drug within microspheres formulation. Sustained drug release profile over 12 h was achieved by PCL polymer. In conclusion, polymeric microspheres containing KFN can be successfully prepared using the technique of experimental design, and these results helped in finding the optimum formulation variables for EE of microspheres.